2016
DOI: 10.1186/s12884-016-1110-x
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma parvum genotype, combined vaginal colonisation with Candida albicans, and spontaneous preterm birth in an Australian cohort of pregnant women

Abstract: BackgroundDetection of Ureaplasma, Mycoplasma and Candida spp. in the vagina during pregnancy has previously been associated with preterm birth (PTB). However, the prevalence of these microorganisms and the associated obstetric risks (likely to be population-specific) have not been determined in Australian women; furthermore, in the case of Ureaplasma spp., very few studies have attempted characterisation at the species level and none have examined genotype/serovar status to further refine risk assessment.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 71 publications
2
59
2
Order By: Relevance
“…In our study, the statistically significant association between U. parvum colonization and SPB was independent of concomitant BV or fungal infection, although the risk for SPB increased significantly in cases with 2 or more of these risk factors present, which is in accordance with previous reports [17,22]. The statistically significant association between lower GA at birth and higher incidence of not only U. parvum colonization, but also diagnosis of BV and fungal infection, suggests that SPB might be a result of polymicrobial infection with U. parvum and other microorganisms in some cases.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In our study, the statistically significant association between U. parvum colonization and SPB was independent of concomitant BV or fungal infection, although the risk for SPB increased significantly in cases with 2 or more of these risk factors present, which is in accordance with previous reports [17,22]. The statistically significant association between lower GA at birth and higher incidence of not only U. parvum colonization, but also diagnosis of BV and fungal infection, suggests that SPB might be a result of polymicrobial infection with U. parvum and other microorganisms in some cases.…”
Section: Discussionsupporting
confidence: 82%
“…A recent report investigated the effect of ureaplasmas in the context of the vaginal microbiome and raised the hypothesis that alterations of the microbiome with an abundance of ureaplasmas as well as other pathogens might increase the risk for adverse pregnancy outcome [22]. In addition, Payne et al [17] hypothesized that the combination of U. parvum and VC might particularly elevate the risk for SPB. Other risk factors for ascending infection might include a short cervix, genetic factors of the host, as well as virulence factors of the pathogen [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial retrospective studies of vaginal specimens from the UPCAN study 18 found interesting results compared to those previously reported in Australasia (Figure 1). The main differences in serotypes compared to other studies are seen for cps Ib, II, VI and IX in our WA cohort.…”
Section: Gbs In Western Australiamentioning
confidence: 58%